Upaya Meningkatkan Kualitas Produk Bakso Berdasarkan Model Kano di CV Mett Ball Foods - Irman Maulana; Dian Jingga Permana (Teknik Industri Universitas Indraprasta PGRI, 2019)
The opportunity for processing food (Bakso) is so large, the intense competition between players in seizing customers requires that the customers can improve the quality of their products based on customer perceptions. This study aims to improve the quality of meatball products based on the Kano model method. The method used in this study uses the Kano method or model combined with eight dimensions of TQM quality or Garvin 1987 dimensions for the goods category. The results showed that there were six attributes belonging to the Must-be category, five attributes belonging to the One-dimensional category, three attributes belonging to the Attractive category and 16 attributes belonging to the Inddiffrent category. The quality improvement priorities that must be made in order to increase customer satisfaction are found in the One-dimensional category of B12, B14, B17, B21 and Attractive Attributes on Attributes B1, B2 and B19.Key words : Customer Satisfaction, Canoe Model, Dimensions of quality (TQM)